The Comprehension of Students’ Ability in Using Causative Verbs in Fourth Semester of English Literature Program, USU - Sianturi, Naomi Elisabeth; Fianda, Afiqah; Silvizi Hijra, Hannah Zakiyya; Ariqah, Nabilah (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2023)
The causative verb is one of a lesson that is discussed in grammar. Learning grammar has never been easy for anyone because of its complexity. The same thing goes for learning causative verbs. It can be both easy and challenging at the same time because sometimes the usage of causative verbs can be confusing. This study was meant to find out how well the ability of the students of the University of Sumatera Utara in the English Department in understanding and applying causative verbs. The method used in this research is the quantitative method. Google Forms is used in this research as the instrument of the research in multiple choices forms. The result is needed to find out the ability of the students to perform causative verbs. The results of this research show that the ability of students of the University of Sumatera Utara in the English Department is in the upper middle category, which is shown from the student’s test results, which is 68%. This research is expected that it will be useful for researchers, students, and teachers in understanding causative verbs.